NOSOCOMIAL PNEUMONIA; RADIOLOGIC DIAGNOSIS IN PRANANGKLOA HOSPITAL - POOLSIRI, SIRIPORN (The ASEAN Journal of Radiology, 2023)
Nosocomial Pneumonia is one of the important complications commonly found in the hospital. Early diagnosis and prompt treatment is essential to decrease morbidity and mortality rate of nosocomial pneumonia. This retrospective study was performed in Pranangkloa Hospital to determine the accuracy of chest radiograph. 163 patients diagnosed as nosocomial pneumonia in Pranangkloa Hospital between October 2001 and September 2004 were included in this study. Medical records and chest radiographs of the patients were studied and reviewed. Percentage and Chi-square were used in data analyses. Finding: Nosocromial pneumonia is commonly occur in male (61.35%) and old aged group (45.39%). The complications were usually found in neurosurgical patients (39.26%) and medical patients (36.20%). The common causative agents are polymicro-organism (56.44%) and gram-negative bacilli (73.23%). Strong association between nosocomial pneumonia and mechanical ventilators was found (93.90%). Chest radiograph was performed in only 65% of the patients, in which positive finding, pulmonary infiltration/consolidation, were 74.53%. Infection in lower lobe, and multifocal or entirely infection were detected in 43.50% and 29.11%, respectively. Chest radiograph is found to be highly accurate in the diagnosis of nosocomial pneumonia (X2=76.57, p=0.000, ∞<0.05) Conclusion: Abnormal chest radiograph is sensitive for early diagnosis of nosocomial pneumonia. Although no specific pattern of abnormal chest radiograph can be identified, strong correlation between abnormal chest radiograph and nosocomial pneumonia was clearly demonstrated, the author suggest that early radiography should be performed in any suspected cases especially in the elderly patients and the group using mechanical ventilators.